IL-1Ra: its role in rheumatoid arthritis - M. Cutolo (PAGEPress Publications, 2011)
Interleukin-1 (IL-1) is one of the pivotal cytokines in initiating and driving the processes of rheumatoid arthritis (RA), and the body's natural response, IL-1 receptor antagonist (IL-1Ra), has been shown conclusively to block its effects. IL-1 mediate several clinical symptoms of the inflammatory reaction (i.e. fever, pain, sleep disturbances). IL-1 is considered a key mediator in RA joint damage because of its greater capacity (greater than TNF) of increasing matrix degradation by inducing the production of MMPs and PGE2 in synovial cells, as well by its role as mediator of bone and cartilage destruction. In addition, IL-1 decreases the repair process by suppressing matrix synthesis and shows a strong synergism with TNF in inducing many inflammatory genes at both local and systemic level. The induced endogenous production of IL-1Ra, in presence of the RA synovitis, is too low to contrast the high affinity of IL-1 for the cell receptors. Therefore, IL-1Ra presence should result in very effective prevention of IL-1 signal transduction particularly in the inflammatory site. In laboratory and animal studies inhibition of IL-1 by either antibodies to IL-1 or IL-1Ra proved beneficial to the outcome. IL-1Ra is a member of the IL-1 superfamily. The effects of different DMARDs on IL-1Ra levels in RA patients support the important role that selected anticytokine treatments might exert in the pathophysiology of the disease. However, since anti TNFα therapy it is not effective in all RA patients, nor does it fully control the arthritic process in affected joints of good responders and complete TNF suppression should be avoided, the combined treatment with intermediate doses of TNF and IL-1 blockers, reaching synergistic suppression of arthritis, seems warranted in RA.